2009
DOI: 10.1002/jor.20834
|View full text |Cite
|
Sign up to set email alerts
|

Tendon degeneration is not mediated by regulation of Toll‐like receptors 2 and 4 in human tenocytes

Abstract: We hypothesized that expression of Toll-like receptors (TLRs) 2 and 4 by tenocytes is involved in the catabolic processes of tendon degeneration. We investigated TLR2 and TLR4 expression by tenocytes in healthy and tendinotic Achilles tendons. We also investigated whether TLR2 and TLR4 could be upregulated in tendon explants using proinflammatory cytokines interleukin (IL)-1b and tumor necrosis factor alphpa (TNFa). Peroperatively harvested healthy (n ¼ 5) and tendinotic (n ¼ 13) Achilles tendon samples were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(25 reference statements)
1
12
0
1
Order By: Relevance
“…In particular, our experiments show that tendon cells sense uric acid but whether it could occur via TLR2 as in chondrocytes is unexplored [25]. Actually, tenocytes express the main receptors involved in sterile inflammation, TLR2 and TLR4, [26], but it is not clear in what circumstances these receptors are functional. Uric acid can also enter the cell via specific transporters where it can modulate inflammatory and oxidative events.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our experiments show that tendon cells sense uric acid but whether it could occur via TLR2 as in chondrocytes is unexplored [25]. Actually, tenocytes express the main receptors involved in sterile inflammation, TLR2 and TLR4, [26], but it is not clear in what circumstances these receptors are functional. Uric acid can also enter the cell via specific transporters where it can modulate inflammatory and oxidative events.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the human Achilles tendon, which is a tendon that is very frequently affected by tendinopathy, especially in the midportion, in principle nothing is known. The only aspect that is known for this tendon is the finding described above concerning the effects of TNF-␣ stimulation on cultured tendon explants, these explants being from Achilles tendon [de Mos et al, 2009]. It is not known…”
Section: Introductionmentioning
confidence: 99%
“…Cultured avian tendon cells exposed to TNF-␣ , an increased temperature, and mechanical stress led to a reduction of procollagen mRNA expression [Pan and Halper, 2003]. Cultured human tenocytes treated with TNF-␣ reduced their type 1 collagen deposition and highly upregulated their expression of pro-and immunoregulatory cytokines [John et al, 2010], and culturing tendon explants in the presence of TNF-␣ led to upregulation of the expression of Toll-like receptor 2 mRNA [de Mos et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to COL5A1, three variants within the MMP3 gene were also found to associate with Achilles tendinopathy in South Africans ). Interestingly previous (Alfredson et al, 2003, Ireland et al, 2001 and more recent data (de Mos et al, 2009, Jelinsky et al, 2011 have shown that MMP3 expression levels are significantly repressed in tissue obtained from Achilles tendinopathic material when compared to controls.…”
Section: Initial Investigationsmentioning
confidence: 91%